2022
DOI: 10.3389/fpubh.2022.975140
|View full text |Cite
|
Sign up to set email alerts
|

Factors interfering with the adoption of good hygiene practices in public school food services in Bahia, Brazil

Abstract: This cross-sectional study aimed to identify factors that interfere with the adoption of good hygiene practices in public school food services (SFS) in Bahia, Brazil. The search was conducted in public schools in Bahia/Brazil. Data collection included (i) evaluation of the adoption of Good Practices in school food services through visual observation and registration in the checklist in Good Hygienic Practices in School Food Services; (ii) Identification of schools' foodservice physical areas and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…Our survey revealed that near half of the knowledge of hygiene practices is poorly understood by food workers, which implies that the knowledge of food handling possessed by professionals who handle food is significantly inadequate. This result is similar to the results of Habte et al (5) survey on food handlers' knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al (32) survey on food handlers' knowledge in Jordan, but lower than the results of Ferreira et al (13) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al (13) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our survey revealed that near half of the knowledge of hygiene practices is poorly understood by food workers, which implies that the knowledge of food handling possessed by professionals who handle food is significantly inadequate. This result is similar to the results of Habte et al (5) survey on food handlers' knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al (32) survey on food handlers' knowledge in Jordan, but lower than the results of Ferreira et al (13) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al (13) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training.…”
Section: Discussionsupporting
confidence: 88%
“…This result is similar to the results of Habte et al (5) survey on food handlers' knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al (32) survey on food handlers' knowledge in Jordan, but lower than the results of Ferreira et al (13) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al (13) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training. Moreover, knowledge was also identified as a significant promoter of worker adherence to hygiene practices, which is consistent with the (12).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations